Safety of biological therapies following rituximab treatment in rheumatoid arthritis patients. Issue 12 (20th January 2009) - Genovese, M C; Breedveld, F C; Emery, P; Cohen, S; Keystone, E; Matteson, E L; Baptiste, Y; Chai, A; Burke, L; Reiss, W; Sweetser, M; Shaw, T M
Abstract : Objective: To assess the safety of biological disease-modifying antirheumatic drugs (DMARD) in rheumatoid arthritis (RA) patients following rituximab. Methods: RA patients who participated in an international rituximab clinical trial programme were included. Patients who had received one or more rituximab courses and entered safety follow-up (SFU) were permitted additional biological DMARD. Serious infection events (SIE) were collected. Results: Of 185 of 2578 patients who entered SFU and received another biological DMARD, 88.6% had peripheral B-cell depletion at the time of initiation of another biological agent. Thirteen SIE (6.99 events/100 patient-years) occurred following rituximab but before another biological DMARD and 10 SIE (5.49 events/100 patient-years) occurred following another biological DMARD. SIE were of typical type and severity for RA patients. 153 had received one or more tumour necrosis factor inhibitor(s). No fatal or opportunistic infections occurred. Conclusions: In this analysis, treatment with biological DMARD after rituximab was not associated with an increased serious infection rate. Sample size with limited follow-up restricts definitive conclusions.